2010
DOI: 10.1016/j.yqres.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary climatic events and sea-level changes recorded by turbidite activity, Dakar Canyon, NW Africa

Abstract: The relationship of sea-level changes and short-term climatic changes with turbidite deposition is poorly documented, although the mechanisms of gravity-driven sediment transport in submarine canyons during sea-level changes have been reported from many regions. This study focuses on the activity of the Dakar Canyon off southern Senegal in response to major glacial/interglacial sea-level shifts and variability in the NW-African continental climate. The sedimentary record from the canyon allows us to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Concurrently, a shelf record displayed distinct dust events during the last 5000 years, suggesting that during several short-lasting drought periods extraordinary increases in dust accumulation in the tributaries of the canyon provided the main trigger for these recurrent turbidites . Similar climate driven turbidite activity during the last 240 kyr is also observed in the Dakar Canyon (Pierau et al, 2010). An initial correlation of turbidite events in the Dakar Canyon and in the Timiris Canyon offshore the hyperarid Sahara showed that both canyons consistently revealed highest turbidite frequencies during late glacial to deglacial times and during Heinrich events.…”
Section: Submarine Canyon Systems Off Nw-africasupporting
confidence: 63%
See 4 more Smart Citations
“…Concurrently, a shelf record displayed distinct dust events during the last 5000 years, suggesting that during several short-lasting drought periods extraordinary increases in dust accumulation in the tributaries of the canyon provided the main trigger for these recurrent turbidites . Similar climate driven turbidite activity during the last 240 kyr is also observed in the Dakar Canyon (Pierau et al, 2010). An initial correlation of turbidite events in the Dakar Canyon and in the Timiris Canyon offshore the hyperarid Sahara showed that both canyons consistently revealed highest turbidite frequencies during late glacial to deglacial times and during Heinrich events.…”
Section: Submarine Canyon Systems Off Nw-africasupporting
confidence: 63%
“…2A). Additionally, core GeoB 9612-3, taken from the northern levee, serves as stratigraphic reference section and monitors shifts in hemipelagic background sedimentation (Pierau et al, 2010). Detailed structural and textural analyses of the turbidite sequences were determined using X-ray radiographies, taken from sediment slides of 1 cm thickness.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations